UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI AKADEMIK DI SD NEGERI 001 GUNUNG KIJANG KEPULAUAN RIAU - Suyatno, Suyatno (Universitas Tanjungpura, 2020)
Performance of teacher is reached result of them in executing based duties of efficiency, seriousness and experience and also usage of time in course of learning to teach in school. Teacher performance will good if teacher have executed elements which consist of and faithfulness of commitment the highness at duty teach, mastering and developing lesson materials, discipline in teaching and other duty, creativity in executing instruction, cooperation with all school citizens, leadership becoming student peer, good personality, ad for andobjective in guiding student, and also responsibility to his duty. Research focused 1. Strategy any kind of done by headmaster in improving teacher rofessionalism in SD Negeri 001 Gunung Kijang Kabupaten Bintan? 2. Factor any kind of becoming supporter and constraint in improvement teacher professionalism in SMP N 4 Gunung Kijang Kabupaten Bintan? 3. How effort the done by headmaster in handling constraint factor of[is make-up of teacher professionalism in SD Negeri 001 Gunung Kijang Kabupaten Bintan? Method Research weared in this research is device qualitative with method intake of data through interview, documentation and observation to informan namely components in SD Negeri 001 Gunung Kijang Kabupaten Bintan. While data analysis through analysis of interaktif.